Enhancing collaborative peer-to-peer systems using resource aggregation and caching: a multi-attribute resource and query aware approach - Bandara, H. M. N. Dilum, author; Jayasumana, Anura P., advisor; Chandrasekar, V., committee member; Massey, Daniel F., committee member; Ray, Indrajit, committee member (Colorado State University. Libraries, 2012)
To view the abstract, please see the full text of the document.
Zip file contains the source code.
A brief description of simulator designs and configuration parameters is found in Appendix II. The simulators were developed using Python.
Keywords: caching; data fusion; named data networking; peer-to-peer; resource discovery; sensor networks